Odpowiedź:
a) x²-5x=0
x(x-5)=0
x=0 x-5= 0
x= 5
b) x²-7x+6=0
a= 1 b= -7 c=6
Δ= b²-4ac
Δ= (-7)²-4*1*6
Δ= 49-24
Δ=25
√Δ= √25= 5
x₁= -b-√Δ/2*a
x₁= -(-7) -5/2*1
x₁= 7-5/2
x₁= 2/2
x₁=1
x₂= -b+√Δ/2*a
x₂= -(-7)+ 5/2*1
x₂= 7+5/2
x₂= 12/2
x₂=6
c) 5x²=125/:5
x²= 25 /√
x= √25
x= 5 lub x= -5
d) 4x-3x²=0
x(4-3x)=0
x=0 4-3x=0
-3x= -4/:(-3)
x= 4/3
f) x-2x²=x²-4
x-2x²-x²+4=0
-3x²+x+4=0
a= -3 b= 1 c=4
Δ=b²-4ac
Δ- 1²-4*(-3)*4
Δ= 1+48
Δ=49
√Δ= √49=7
x₁= -b-√Δ/2*a
x₁= -1-7/2*(-3)
x₁= -8/-6
x₁= 8/6
x₁= 1 2/6= 1 1/3
x₂= -b+√Δ/2*a
x²= -1+7/2*(-3)
x₂= 6/-6
x₂= -1